Basin‐scale assessment of the land surface energy budget in the National Centers for Environmental Prediction operational and research NLDAS‐2 systems. Issue 1 (14th January 2016) - Xia, Youlong; Cosgrove, Brian A.; Mitchell, Kenneth E.; Peters‐Lidard, Christa D.; Ek, Michael B.; Kumar, Sujay; Mocko, David; Wei, Helin
Abstract: This paper compares the annual and monthly components of the simulated energy budget from the North American Land Data Assimilation System phase 2 (NLDAS‐2) with reference products over the domains of the 12 River Forecast Centers (RFCs) of the continental United States (CONUS). The simulations are calculated from both operational and research versions of NLDAS‐2. The reference radiation components are obtained from the National Aeronautics and Space Administration Surface Radiation Budget product. The reference sensible and latent heat fluxes are obtained from a multitree ensemble method applied to gridded FLUXNET data from the Max Planck Institute, Germany. As these references are obtained from different data sources, they cannot fully close the energy budget, although the range of closure error is less than 15% for mean annual results. The analysis here demonstrates the usefulness of basin‐scale surface energy budget analysis for evaluating model skill and deficiencies. The operational (i.e., Noah, Mosaic, and VIC) and research (i.e., Noah‐I and VIC4.0.5) NLDAS‐2 land surface models exhibit similarities and differences in depicting basin‐averaged energy components. For example, the energy components of the five models have similar seasonal cycles, but with different magnitudes. Generally, Noah and VIC overestimate (underestimate) sensible (latent) heat flux over several RFCs of the eastern CONUS. In contrast, Mosaic underestimates (overestimates) sensible (latent) heat flux over almost all 12 RFCs. The research Noah‐I and VIC4.0.5 versions show moderate‐to‐large improvements (basin and model dependent) relative to their operational versions, which indicates likely pathways for future improvements in the operational NLDAS‐2 system. Key Points: To assess basin‐scale energy components in NCEP operational and research NLDAS‐2 To jointly use GEWEX/SRB radiation and gridded FLUXNET‐based energy fluxes To directly evaluate NLDAS‐2 energy products at 12 CONUS River Forecast Centers